Epidemiology of exertional heat illnesses in National Collegiate Athletic Association athletes during the 2009-2010 through 2014-2015 academic years - Yeargin, S. W.; Dompier, T. P.; Casa, D. J.; Hirschhorn, R. M.; Kerr, Z. Y. (Journal of Athletic Training, 2019)
Context Exertional heat illnesses (EHIs) among football athletes have been widely researched, but data examining all collegiate sports are limited.